Alternative splicing in human myeloid cell differentiation and leukaemia - Lim, Kai Yi (Nanyang Technological University, 2021)
Dysregulation of alternative splicing (AS) has been implicated in aberrant cell function, resulting in diseases such as acute myeloid leukaemia (AML). It was found that myeloid cell differentiation was impaired due to mutations and altered expression levels of splicing factors (SFs). Preliminary data has shown RNA-binding motif protein 47 (RBM47) to be one of the upregulated SFs in AML cells. In this study, effect of RBM47 expression levels on myeloid cell differentiation was studied using HL-60 as a differentiation model. HL-60 overexpressing RBM47 was differentiated alongside wild-type and the extent of differentiation was measured and compared. We found that RBM47 overexpression in differentiating HL-60 cells increased surface expression of maturation markers, elevated baseline ROS levels and improved phagocytic ability. Meanwhile, overexpressing RBM47 did not alter untreated, undifferentiated cells. RBM47-regulation of AS in HL-60 was also investigated, and we report that inclusion of exon 12 in MAP3K7 mRNA was induced by RBM47. Findings of this study suggest that RBM47 overexpression supports myeloid cell differentiation by accelerating the process after initiation by other factors. It is possible that RBM47 achieves this effect through AS of several key genes in cell differentiation, though more work is required before conclusions can be drawn.